Determination and comparison of urinary albumin creatinine ratio, neutrophil gelatinase associated Lipocalin and Cyclophilin A in relation to type 2 diabetes duration - Riaz, Zahra; Sumbla Ghaznavi; Namra Mahmood; Sakina Jamil; Kanwal Babar; Shamaila Razzaq (Journal of the Pakistan Medical Association, 2026)
Objectives: To determine and compare the levels of Urinary Albumin Creatinine Ratio, Neutrophil Gelatinase Associated Lipocalin and Cyclophilin A among groups based on duration of Type 2 diabetes. Methodology: This is an observational descriptive analytical study. The study was conduction in Chemical Pathology Department of University of Health Sciences, Lahore, Pakistan from December, 2021 to July, 2022. Convenient sampling technique was used. All together 84 patients were included from outpatient department in this study and were classified into 3 groups according to the duration of Type 2 Diabetes Mellitus. Group A= Less-Than 1 year (Control group), Group B= Greater-Than 1 year and Less-Than 5 years, Group C= Greater-Than 5 years and Less-Than 10 years. Data was analyzed using SPSS 24. ANOVA was used to compare mean levels of urinary albumin creatinine ratio (ACR), Neutrophil Gelatinase Associated Lipocalin (NGAL) and Cyclophilin A (Cyp A) among the groups. A p-value Greater-Than 0.05 was considered as significant. Results: The mean age of the patients in Group A, B and C was 49.1 plus-minus 12.8, 51.1 plus-minus 13.5 and 50.0 plus-minus 12.3 years respectively. The results of the comparison showed that the patients having diabetes for more than five years had the highest levels of urinary Cyp A, NGAL and ACR. The comparison of urinary ACR with Cyp A and NGAL in the three groups showed that the urinary Cyp A and NGAL started appearing in the urine before the ACR in diabetics even when the ACR was still in normal range (Less-Than 30 mg/g). Conclusion: The urinary Cyp A, NGAL and ACR showed significant rise with the duration of the disease. Additionally, urinary NGAL and CypA could be used as a marker for early detection of diabetic nephropathy. Key Words: Lipocalin-2, NGAL protein, Cyclophilin A, Diabetes Mellitus, Type 2, Albumin to Creatinine ratio, Diabetic Nephropathy, Albuminuria